Antibiotic resistance and Staphylococcal super antigenic determinants in methicillin resistant Staphylococcus aureus isolated from anterior nares of dental students - Vinshia, Jebadass Jasmine; Padmavathy, Kesavaram; Sudha, Jimson; Sathyapriya, Baskaran (Journal of Applied Pharmaceutical Research, 2023)
Background: Staphylococcus aureus primarily inhabits the human anterior nares. Asymptomatic Methicillin-resistant Staphylococcus aureus (MRSA) nasal carriage in healthcare professionals makes them potential MRSA reservoirs. Since identification and decolonization would promote cross-contamination reduction and curb communal transmission, this study was designed to identify MRSA nasal carriers among dental students and detect staphylococcal super antigenic determinants among them. Methods: Staphylococci isolates (n=52) from dental students(n=42) were investigated in the study. Following initial microbial speciation and antimicrobial susceptibility determination using standard identification methods, the MRSA strains were identified phenotypically using cefoxitin disc (30 µg). Genes encoding the virulence determinants, namely, TSST (test), enterotoxins (sea and seb), and cytotoxin (pvl), were looked for by PCR. Results: Only 15.09% of isolates were identified as Staphylococcus aureus, and all of them (n=8) were scored as MRSA using the cefoxitin disc diffusion method. None of the tested isolates showed the presence of virulence determinants in standard molecular techniques. Conclusion: Lower prevalence of S. aureus, MRSA, coupled with the absence of virulence determinants in the strains, suggests strategies for better surveillance. Tracking virulence-causing genes in nasal carrier S. aureus strains could enhance efforts to prevent infection outbreaks.